Job Rotation, Job Enrichment and Job Enlargement on Employee Performance - Intan Hermila Utari; Sulastri Sulastri (Human Resource Management Studies, 2022)
This study aims to determine the effect of job rotation, job enrichment, and job enlargement on employee performance at PT. West Sumatra Regional Development Bank (Main Branch). The population and samples used in this study were employees of PT. West Sumatra Regional Development Bank (Main Branch) which opened 101 employees. The sample used in this study was 81 employees. The sampling technique is proportional cluster simple random sampling. The analytical technique used is multiple linear analysis with SPSS 25. The results of this study indicate that: (1) job rotation has a positive and significant effect on employee performance at PT. West Sumatra Regional Development Bank (Bank Nagari) Main Branch (2) job enrichment has a positive and significant effect on employee performance at PT. West Sumatra Regional Development Bank (Bank Nagari) Main Branch (3) job enlargement has a positive and significant effect on employee performance at PT. West Sumatra Regional Development Bank (Bank Nagari) Main Branch (4) job rotation, job enrichment, and job enlargement have a significant effect on employee performance at PT. West Sumatra Regional Development Bank (Bank Nagari) Main Branch.